2019
DOI: 10.1097/ta.0000000000002471
|View full text |Cite
|
Sign up to set email alerts
|

Cold-stored whole blood: A better method of trauma resuscitation?

Abstract: BACKGROUND Cold-stored whole blood (CWB) provides a balance of red blood cells, plasma, and platelets in less anticoagulant volume than standard blood component therapy (BCT). We hypothesize that patients receiving CWB along with BCT have improved survival compared with patients receiving only BCT. METHODS We performed a dual-center case-match study of trauma patients who received CWB and BCT at two urban, Level-I Trauma Centers. Criteria to receive CWB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 22 publications
3
48
0
1
Order By: Relevance
“…Nessen et al showed that, in the experience with Forward Surgical Teams (FSTs) in Afghanistan, use of FWB in addition to RBCs and FFP was associated with improved inhospital survival compared to RBCs and FFP alone 19 . Within the civilian sector, retrospective analyses suggest superiority or equivalence of WB with regards to mortality and overall blood product use [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Nessen et al showed that, in the experience with Forward Surgical Teams (FSTs) in Afghanistan, use of FWB in addition to RBCs and FFP was associated with improved inhospital survival compared to RBCs and FFP alone 19 . Within the civilian sector, retrospective analyses suggest superiority or equivalence of WB with regards to mortality and overall blood product use [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study in two civilian level 1 trauma centers showed that injured patients resuscitated with CWB had higher hematocrits and decreased trauma bay mortality compared to those resuscitated with component therapy. However; there was no difference in total amounts of blood products transfused and no difference in 30-day mortality between these two groups (43). Chilled whole blood has been used to treat US combat casualties at the point of injury since 2016 and, according to US military clinical practice guidelines, is the preferred resuscitation product for pre-hospital transfusion (44).…”
Section: Chilled Whole Bloodmentioning
confidence: 99%
“…Historically, prehospital resuscitation by first responders for point‐of‐injury or en route care was restricted to crystalloid or colloid saline‐based solutions with the occasional adjunct such as tranexamic acid administered. Recently, much evidence has been put forth demonstrating the superiority of using blood and blood products for hemostatic resuscitation, especially in traumatic hemorrhage cases 5–9 . The military has made great strides in providing early resuscitation through programs such as the low titer group O whole blood (LTOWB) effort 10, 11 which is now propagating into the civilian realm 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, much evidence has been put forth demonstrating the superiority of using blood and blood products for hemostatic resuscitation, especially in traumatic hemorrhage cases. [5][6][7][8][9] The military has made great strides in providing early resuscitation through programs such as the low titer group O whole blood (LTOWB) effort 10,11 which is now propagating into the civilian realm. 12,13 With the exception of the recent wars in the Middle East, blood rarely has been available pre-hospital in both civilian and military realms.…”
Section: Introductionmentioning
confidence: 99%